Визначення строків сівби та терміну зберігання насіння видів роду Monarda L. в умовах інтродукції в Північному Лісостепу України - Rys, M.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The term of the sowing and storage period of seeds of aromatic plants of genus Monarda L. under condition of introduction in North Forest-Steppe of Ukraine were determined. Two perspective forms of Monarda didyma L. with different colors of flowers and leaves were selected and described.